CRISPR-Cas9 effectors facilitate generation of single-sex litters and sex-specific phenotypes - Charlotte Douglas (Nature Portfolio, 2021)
In areas such as animal research and agriculture a single sex is often required in abundance, leading to wasted resources and ethical considerations. Here the authors develop a CRISPR/Cas9 mediated synthetic lethal system that enables the production of single sex offspring that can be repurposed for use in multiple organisms.